Regular exercise counteracts circadian shifts in core body temperature during long-duration bed rest - Stefan Mendt (Nature Portfolio, 2021)
Abstract With NASA’s plans for the human exploration of Mars, astronauts will be exposed to mission durations much longer than current spaceflight missions on the International Space Station. These mission durations will increase the risk for circadian misalignment. Exercise has gained increasing interest as a non-pharmacological aid to entrain the circadian system. To assess the potential of exercise as a countermeasure to mitigate the risk for circadian disorders during spaceflight, we investigated the effects of long-term head-down tilt bed rest (HDBR) with and without exercise on the circadian rhythm of core body temperature. Core body temperature was recorded for 24 h using a rectal probe in sixteen healthy men (age: 30.5 ± 7.5 years (mean ± SD)) after 7 days and 49 days of HDBR. Five participants underwent HDBR only (CTR), five participants underwent HDBR and performed resistive exercises (RE), and six participants underwent HDBR and performed resistive exercises superimposed with vibrations (RVE). The exercise was scheduled three times per week. CTR showed a phase delay of 0.69 h. In contrast, both exercise groups were characterized by a phase advance (0.45 h for RE and 0.45 h for RVE; p = 0.026 for interaction between time and group). These findings suggest that resistive exercise (with or without vibration) may also serve as a countermeasure during spaceflight to mitigate circadian misalignments. The results could also be important for increasing awareness about the role of circadian disorders in long-term bedridden patients.